Impact of Information and Communication Technologies (ICTs) on agriculture practices - KUMAR, RUPENDER; HUDDA, R S; YADAV, KRISHAN; MANJEET, MANJEET (The Indian Journal of Agricultural Sciences, 2018)
The present study was carried out in four districts of Haryana state, i.e. Yamunanagar, Karnal, Hisar and Fatehabad which were selected randomly. In total 240 respondents, viz. 60 farmers from each district, 30 farmers from each block and 15 farmers from each village were selected for present study. Majority of farmers used ICTs for knowing source of quality seeds, suitable high-yielding variety for the specific area. Most of the farmers used ICTs in nursery management for plant protection measures, method of preparing bed and nutrient management. Farmers used ICTs for the information purpose like price of fertilizers and stock of fertilizers. Farmers used ICTs for chemical weed management, price of weedicides, and place of availability, trade names and stock availability. ICTs use for the information purpose, for scheduling irrigation followed by to know critical stages of irrigation application and fertilizer management during irrigation. Farmers used ICTs for identification, nature of damage and control measures for insects/pests of different crops. Majority of the farmers used ICTs for the purpose of information, ideal thrasher for thrashing of crops followed by proper timing of harvesting. The correlation and regression of different variables, i.e. education, socio-economic status, land holding, extension contact, mass media exposure, scientific orientation, economic motivation and risk orientation exhibited positive and significant effect, whereas age exhibited negative and significant effect. However, irrigation facilities exhibited non-significant effect but it positively correlated with agricultural practices.